Platforma soczewkowa - Łukaszewska-Smyk, Agnieszka; Kałużny, Józef (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
The lens platform defines lens structure and lens material. Evolution of lens comprises change in their shape, angulation of haptens and transition of three-piece lens into one- piece lens. The lens fall into two categories: rigid (PMMA) and soft (siliconic, acrylic, colameric). The main lens materials are polymers (hydrophilic and hydrophobic). The lens platform has an effect on biocompatibility, bioadhesion, stability of lens in capsule, degree of PCO evolution and sensitiveness to laser damages.